Photoinduced inhibition of DNA unwinding in vitro with water-soluble polymers containing both phosphorylcholine and photoreactive groups. (August 2016) - Lin, Xiaojie; Fukazawa, Kyoko; Ishihara, Kazuhiko
Graphical abstract: Abstract: Nile blue (NB)-tagged DNA helix-targeting amphiphilic photoreactive 2-methacryloyloxyethyl phosphorylcholine (MPC) polymer, poly(MPC- co -3-methacryloyloxy-2-hydroxypropyl-4-oxybenzophenone- co -2-trimethylammonium ethyl methacrylate chloride) (PMHT–NB), containing a cationic group to facilitate cell membrane penetration and a benzophenone (BP) group to promote photoinduced conjugation with DNA helix was synthesized using radical polymerization method. Ultraviolet light (UV)-visible light absorption spectra of PMHT–NB showed absorption peaks at wavelengths 254, 289, and 600 nm, suggesting successful incorporation of BP and NB groups. PMHT–NB was highly sensitive to photoirradiation with UV irradiation at the second level, as confirmed based on the degradation spectra of UV absorption peaks for the BP group in PBS (pH = 7.4). PMHT–NB showed good solubility in both aqueous solution and in ethanol. In a cell culture medium containing 10 mg/mL PMHT–NB, the NB group showed fluorescence peaks at an emission wavelength of 650 nm and excitation wavelength of 633 nm. PMHT–NB also showed low cytotoxicity and good cell membrane permeability toward cancerous HeLa cells. Further, photoinduced PMHT–NB effectively inhibited the unwinding of a molecular beacon with a hairpin structure, indicating that synthetic photoreactive MPC polymers photoregulated the unwinding of DNA. Statement of Significance: Natural and synthetic genetic hybrid biomaterials consisting of well-designed polymers loaded with oligonucleotide fragments are considered as an attractive alternative to conventional transgene systems and chemical methods for precisely and rapidly modulation of intracellular gene expression. Containing versatile functional moieties, the effectiveness of well-designed cytocompatible polymers themselves without oligonucleotide fragments on gene regulation is rarely investigated. In the present study, a 2-methacryloyloxyethyl phosphorylcholine (MPC) polymer composed of a tumor/DNA-targeting moiety and photo-controllable unit demonstrated low cytotoxicity, rapid cell membrane permeability and effective inhibitive ability on DNA unwinding under a light irradiation. The synthetic polymer was considered as promising material to effectively inhibit intracellular partial DNA unwinding for cancer/gene therapy.